Remember that when you multiply exponential functions, you add the exponents if the bases of the functions are the same. Therefore, a^(u+v) = (a^u)*(a^v) = f(u)*f(v)
f(2x) = a^(2x)=a^(x*2)=(a^x)^2=[f(x)]^2
When you raise an exponent to an exponent (a^x)^2, you can multiply those exponents (a^x)^2 = a^(2x). This problems asks you to go in reverse and notice that a^(2x) is the same as a^(x*2), which is the same as [a^x]^2.
Nov 8th, 2014
Studypool's Notebank makes it easy to buy and sell old notes, study guides, reviews, etc.